Interpretation Strategies and Interpretation Performance in Interlingual and Bilingual Subtitling: A Case of Iranian BA Translation Students - Modarresi, Ghasem; Jalilzadeh, Kaveh; Zolfaghary , Raheleh (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2020)
The researchers in Interpreting Studies have underrated the importance of interpretation strategies in interpretation courses at the university level in the Iranian context. As a mixed-method study, the present study mainly aimed at discovering the subtitling strategies used in interlingual subtitling and bilingual subtitling by translation students. The researchers selected 30 homogeneous students majoring in Translation Studies which were divided into two experimental groups. During the treatment phase, the researchers worked with each group's students on subtitling strategies on a comedy film, following Peterson's (2005) strategies. The results of the post-tests confirmed that there was a significant difference for interlingual subtitling since the students’ scores increased significantly from the mean score of 24.53 to the mean score of 27.66 as well as for bilingual subtitling since the students’ scores increased significantly from the mean score of 22.80 to the mean score of 27.13. However, the results revealed no significant difference in students' interpretation scores for interlingual and bilingual subjects. The results of the interviews also supported the effectiveness of audio-visual activities on oral translation. Translation students should pay attention to how they foster their interpreting competence and find the type of subtitling that is more beneficial.